Role of microRNA miR-34a in liver cancer stem cells (Bangladesh Journal of Pharmacology, 2016)
The present study focuses on the role of microRNA miR-34a in liver cancer stem cells. Liver tissue samples were collected from the control and liver cancer patients. Immunohistochemistry experiment with CD90 antibodies suggests that the liver cancer stem cells were present in the liver cancer tissue samples. Interestingly, flow cytometry analysis followed by qRT-PCR confirmed that the CD90+ cells also called as liver cancer stem cells shows expression of miR-34a at the levels of 30-80%, when compared with that of normal liver tissue samples. The present study concludes that the liver cancer stem cells shows high expression of miR-34a, which is the important target unique to liver cancer stem cells in order to design liver cancer stem cells-specific therapies.